2016
DOI: 10.1038/bjc.2015.455
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction and marriage among male survivors of cancer in childhood, adolescence and young adulthood: a national cohort study

Abstract: Background:Increased survival after cancer in young age has made long-term follow-up studies of high external validity important. In this national cohort study, we explored the impact of cancer in young age on reproduction and marital status in male survivors.Methods:Hazard ratios (HRs) and relative risks (RRs) of reproductive and marital outcomes were studied for male survivors of cancer in young age (<25 years) and cancer-free male comparisons, born during 1965–1985, by linking compulsory national registries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 54 publications
(67 reference statements)
3
55
1
1
Order By: Relevance
“…[77][78][79][80] The impact of cancer treatment on fertility is related to the age of the patient at the time of diagnosis and treatment and depends on the type, duration, and dose intensity of treatment. Alkylating agent-based chemotherapy, high-dose cranial RT that can impair hypothalamic pituitary function, and targeted RT to the uterus, ovaries, or testes are primary risk factors for gonadal dysfunction and decreased fertility in both females and males.…”
Section: Impact Of Cancer and Its Treatment On Fertilitymentioning
confidence: 99%
“…[77][78][79][80] The impact of cancer treatment on fertility is related to the age of the patient at the time of diagnosis and treatment and depends on the type, duration, and dose intensity of treatment. Alkylating agent-based chemotherapy, high-dose cranial RT that can impair hypothalamic pituitary function, and targeted RT to the uterus, ovaries, or testes are primary risk factors for gonadal dysfunction and decreased fertility in both females and males.…”
Section: Impact Of Cancer and Its Treatment On Fertilitymentioning
confidence: 99%
“…Due to variability in previous findings, there may be other factors relevant for psychosexual development among childhood cancer survivors, such as type of diagnosis or treatment. One study indicated that brain tumor survivors and those treated with highly neurotoxic modalities were less likely to have had their sexual debut, 7 while other studies found lower attainment of adult psychosexual milestones among brain tumor survivors, such as getting married . Moreover, psychosexual development seems to differ by sex in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…One study indicated that brain tumor survivors and those treated with highly neurotoxic modalities were less likely to have had their sexual debut, 7 while other studies found lower attainment of adult psychosexual milestones among brain tumor survivors, such as getting married. 3,[12][13][14][15] Moreover, psychosexual development seems to differ by sex in the general population. In early adolescence, boys tend to be more likely to engage in sexual activities (ie, 18% vs 13% of girls), but by age 19 rates of sexual debut are nearly equivalent at 69% of boys and 68% of girls.…”
Section: Introductionmentioning
confidence: 99%
“…18 Survivors also were less likely to achieve milestones of psychosexual development, such as being less sexually experienced, [19][20][21][22] older at the time of sexual debut, 19,20,23 less likely to have children, 20,[24][25][26] or reporting problems in sexual functioning. [27][28][29][30][31][32][33] Several studies also found survivors were less likely to marry than siblings/peers, 20,23,[34][35][36][37][38][39] with survivors of brain tumors 20,[34][35][36][37][38] or those treated with radiation 36,39 least likely to marry. Nevertheless, marriage rates comparable to those of controls also have been reported.…”
Section: Introductionmentioning
confidence: 99%